Implementation of the EMC2 Approach as a Strategy to Improve Psychological Well-Being of Grade III Students of Podorejo 3 Elementary School - Yuliana, Yuliana; Zharifah, Izdihar Afaf; Miftahurrozzaq, Muhammad; Saputri, Fariza Ika; Irvan, Moh. Farizqo (Jurnal Riset Ilmu Pendidikan, 2025)
This study aimed to implement the Empathy, Mindfulness, Compassion, and Critical Inquiry approach as a strategy to improve the psychological well-being of third-grade students at SD Negeri Podorejo 3. The research employed a descriptive qualitative approach using a case study method. Data were collected through observation, interviews, and documentation. The findings indicated that the approach successfully promoted the development of students' critical thinking, as reflected in increased confidence during discussions, the ability to express opinions, and thoughtful responses to classroom issues. However, the dimensions of empathy and compassion required further reinforcement, particularly in fostering supportive and caring social relationships among students. Challenges encountered included a competitive classroom atmosphere, lack of discipline, and teachers’ limited capacity to guide students' emotional development. Based on these findings, the approach is recommended for sustainable implementation alongside teacher training to support students’ social and emotional competence. This strategy is expected to help create an inclusive, nurturing, and supportive learning environment that fosters students' psychological well-being.